Choral singing tendencies in comprehernsive schools for pupils aged 11-12 - Kepule, Iveta (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
At present a new view of culture as a source of creativity and a means of developing a personality’s creative abilities has been shaping in Latvia. It emphasizes a significant contribution of culture to other spheres of the country’s development including education, science and art. Choral music lessons an directed at all pupils, therefore, the aim of the lessons is the full development of each pupil’s musical and choral singing abilities, however, the study analysed in the article, books at different opinions of the 11-12-year-old pupils on choral singing lessons. The aim of the article is to highlight the necessity of choral singing in comprehensive schools in connection with the conclusions drawn in H.Gardner’s „Five Minds for the Future”.